2008
DOI: 10.1021/ac701888e
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Investigation into the Correlation between Mass and Ion Mobility for Choline and Other Ammonium Cations in N2

Abstract: A number of tertiary amine and quaternary ammonium cations spanning a mass range of 60-146 amu (trimethylamine, tetramethylammonium, trimethylethylammonium, N,N-dimethylaminoethanol, choline, N,N-dimethylglycine, betaine, acetylcholine, (3-carboxypropyl)trimethylammonium) were investigated using electrospray ionization ion mobility spectrometry. Measured ion mobilities demonstrate a high correlation between mass and mobility in N(2). In addition, identical mobilities within experimental uncertainties are obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
97
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(102 citation statements)
references
References 47 publications
(58 reference statements)
5
97
0
Order By: Relevance
“…CB [6]-MIA complex shows the largest [29]. The observed overall difference of Ω D of complex is caused by relatively small differences of binding geometries and sizes of small haloacetate anions [43]. A relatively small difference between MBA and MCA is difficult to be fully resolved using ion mobility separation technique in the present study.…”
Section: Ion Mobility Study Of Cb[6]-haloacetate and Cb[6]-halide Commentioning
confidence: 67%
“…CB [6]-MIA complex shows the largest [29]. The observed overall difference of Ω D of complex is caused by relatively small differences of binding geometries and sizes of small haloacetate anions [43]. A relatively small difference between MBA and MCA is difficult to be fully resolved using ion mobility separation technique in the present study.…”
Section: Ion Mobility Study Of Cb[6]-haloacetate and Cb[6]-halide Commentioning
confidence: 67%
“…A useful early review is that of Castleman and Keesee, but there are a number of more recent studies, including those from the Leone group[51], and others. A quantitative analysis of comparative modifier effects appears possible based on thermochemical free energy values from computational chemistry, optimized conformations considering energetics and steric hindrance, combined with computations of mobility [22, 52, 53] from predicted structures, and further investigations are in progress. The schema and thermochemistry for ion-cluster / modifier equilibria is summarized in Appendix A.…”
Section: Resultsmentioning
confidence: 99%
“…Although limited structural parameters were reported, these structures appear to correspond to ACh01, ACh02, ACh04, and ACh05. A recent B3-LYP/6-31G(d,p) study by Kim et al [27], carried out to complement their ion mobility studies of tertiary amines and quaternary ammonium cations, found a global minimum that closely resembles ACh01.…”
Section: Dft Calculations On the Conformations Of Acetylcholinementioning
confidence: 99%